(untitled) (Oxford, 1993)
This book includes highly systematic skills development work, organized through a unique skills development sub-syllabus; detailed treatment of grammar in two stages: first within the unit where it is introduced, and then, in a fuller version suitable for self-study and revision, in the Grammar section at the back of the book; a three-prolonged approach to vocabulary expansion consisting of learning strategies, vocabulary systems, and lexical sets.
Keywords: English language,English language; Spoken English